VD_FINDINFO HC / 2011 / 57 vom 2. Februar 2011 - VD Tribunal cantonal (2011)
BAIL À LOYER, DEMEURE DU DÉBITEUR, LOYER, EXPULSION DE LOCATAIRE, SUCCESSION, MORT | 257d CO, 457 CPC, 23 LPEBL, 29 LPEBL, 405 al. 1 CPC (CH)